Menuju Desa Mandiri Budaya: Penguatan Kelembagaan Desa Budaya Kalurahan Wirokerten, Bantul, Yogyakarta - Anwar Kholid; Sakir Sakir; Rivaldi Alan Saputra (Warta LPM, 2024)
The community service of Universitas Muhammadiyah Yogyakarta (UMY) was carried out in Wirokerten, Bantul Regency, Special Region of Yogyakarta. The aims of this project are the strengthening of the cultural village institution and the conservation of Wirokerten culture. These aims are linked to Wirokerten’s vision to get accreditation for Cultural Self-sufficient Village. The achievement indicators for the institutional strengthening are the formulation of the cultural village managers’ job descriptions and work plans. Meanwhile, the achievement indicator for cultural conservation is the compilation of a cultural profile book that contains a list of cultural inventories and mappings. These documents are requirements for the accreditation of cultural villages by the Cultural Office of Bantul Regency. The implementation of this community service is divided into three stages: the initial assessment stage, the implementation stage, and the monitoring and evaluation stage. The methods used are observation, in-depth interviews, benchmarking, and workshops based on the Asset Based Community Development (ABCD) approach. The implementation of this community service successfully fulfilled all the success indicators set. These achievements indicate that there is institutional strengthening of the Wirokerten Cultural Village and that UMY's community service in Wirokerten Village has been successful.